Customer comfort limit utilisation: Management tool informing credit limit-setting strategy decisions to improve profitability - Karmi Visser; Gerbus Swart; Joggie Pretorius; Lin-Marie Esterhuyzen; Tanja Verster; Erika Fourie (Cogent Economics & Finance, 2022)
The key criteria for making business decisions is profit, so when making credit limit-setting strategy decisions, profitability will be the most important driver. The profitability of a credit limit-setting strategy is dependent on the customer's utilisation of the limits set by the strategy. This points towards a need to determine the extent to which a limit can be increased before a customer's utilisation will decline beyond the point of being profitable. This paper sets out to define a Customer Comfort Limit Utilisation (CCLU) measure that can be used to gauge a customer's level of comfort (in terms of limit utilisation) with a newly proposed limit. The CCLU is defined as a function of the customer's limit utilisation and credit limit; in simpler terms, it can be viewed as a function of balance growth vs limit growth. The neural network model that predicted utilisation first and then the CCLU based on the resulting utilisation values was selected as the final model. Once the final model was determined, it was then verified whether profitability could be improved by using a CCLU measure as a management tool when making limit-setting strategy decisions. It was found that strategies involving CCLU values could lead to increased profitability since CCLU values near 100 (i.e. the customer is 100% comfortable with the new limit and will utilise to the same extent as the previous one) are associated with higher key performance metrics levels.
Keywords: 330; credit card limits; prediction; utilisation; customer comfort; profitability; limit strategies; management tool